The Common and Distinct Features of Brown and Beige Adipocytes. (March 2018) - Ikeda, Kenji; Maretich, Pema; Kajimura, Shingo
Abstract : Two types of thermogenic fat cells, brown adipocytes and beige adipocytes, play a key role in the regulation of systemic energy homeostasis in mammals. Both brown fat and beige fat possess thermogenic properties in addition to common morphological and biochemical characteristics, including multilocular lipid droplets and cristae-dense mitochondria. Recent studies also identify features that are distinct between the two types of thermogenic fat cells, such as their developmental regulation and function. Of particular interest is the role of beige fat in the regulation of glucose homeostasis via uncoupling protein 1 (UCP1)-independent mechanisms. A better understanding of the underlying causes of these characteristics of brown and beige fat will allow us to specifically manipulate these cells to improve systemic energy metabolism and glucose homeostasis. Highlights: Two types of thermogenic fat (brown adipocytes and beige adipocytes) are present in humans and rodents. Brown and beige fat possess both common and distinct characteristics that include their developmental regulation and function. Non-canonical (UCP1-independent) thermogenic mechanisms control systemic energy metabolism and glucose homeostasis. Non-canonical thermogenesis by SEARCA2b-mediated Ca 2+ cycling is an evolutionarily conserved mechanism that is active even in animals that lack a functional UCP1 protein.